2007
DOI: 10.1038/sj.ejcn.1602817
|View full text |Cite|
|
Sign up to set email alerts
|

Fish oil after abdominal aorta aneurysm surgery

Abstract: Objective: Fish oil (FO) may attenuate the inflammatory response after major surgery such as abdominal aortic aneurysm (AAA) surgery. We aimed at evaluating the clinical impact and safety aspects of a FO containing parenteral nutrition (PN) after AAA surgery. Methods: Intervention consisted in 4 days of either standard (STD: Lipofundin medium-chain triglyceride (MCT): long-chain triglyceride (LCT)50%-MCT50%) or FO containing PN (FO: Lipoplus: LCT40%-MCT50%-FO10%). Energy target were set at 1.3 times the preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 28 publications
(31 reference statements)
1
91
0
9
Order By: Relevance
“…Eight studies reported this outcome [11,12,15,23,24,26,27,32]. The analysis showed a significant decrease in HLOS within the intervention group compared with the control group.…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies reported this outcome [11,12,15,23,24,26,27,32]. The analysis showed a significant decrease in HLOS within the intervention group compared with the control group.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Figure 1 shows the process for identifying potentially eligible studies and exclusion criteria. After elaborative screening, 34 articles were assessed by full text and 17 studies with 753 patients [2,[10][11][12]15,16,[23][24][25][26][27][28][29][30][31][32][33] were included for the review. However, three publications [2,24,30,31,33] are same study that reported different outcomes.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of 3 fatty acids as part of nutritional intervention in ESRV might also result in stabilization of the atherosclerotic plaque, thus facilitating the work of angiologist surgeon [39]. Morever, it has been reported that use of parenteral lipids solutions incorporating fish oil as a source of 3 fatty acids shortened hospital length of stay of patients electively subjected to abdominal aortic aneurysm surgery [40]. However, is should be remembered that prolonged use of 3 fatty acids might modify shape, size, distribution and lipid composition of HDL High density Lipoproteins that have been linked to a reduced risk of atherosclerotic damage [41].…”
Section: On Perioperatory Nutritional Intervention In Esrvmentioning
confidence: 99%
“…In a recently published study that used MCT-soyabean oil or Lipoplus in patients in the ICU who had undergone abdominal aorta aneurysm repair surgery no differences were found in glucose metabolism or in inflammatory markers (52) . Furthermore, clinical outcomes were not reported to be affected, but a trend was found towards shorter ICU stay (1 .…”
Section: Studies Of Fish Oil In Patients Following Surgerymentioning
confidence: 99%